Assessing the success behind the use of education management information systems in higher education - Martins, José (2019)
The continuous use of dynamic and disruptive ICT as energizing elements of the educational process is a reality of current days, where millennials are the centre of an education paradigm in which students are much more inclined to use technologies than enrolling in a traditional non-digital course. Considering education management information systems (EMIS) capacities to collect, analyse, process and publish information and data, it is easy to perceive their relevance to both education organizations and students. Nevertheless, and despite EMIS complexity and inherent possibilities, the existing literature does not provide for a detailed characterization on the impact these systems might have on students’ success. Thus, this research focuses on understanding the use of EMIS by students and the arising of net benefits; it introduces an EMIS success model which posits that to ensure net benefits for students, education institutions must safeguard that their education management information systems are of high quality, while at the same time students are maintained satisfied with the system and engage in continuous use. To assess the posed model, an empirical study has been performed, involving students from higher education institutions. Findings from the study allow us to perceive that, as information systems (IS) success models state, EMIS use and students’ satisfaction are predictors of net benefits. This same model also claims that the available information quality and EMIS inherent service quality are also strong determinants of both continuous EMIS use and student satisfaction.